Identification and Mapping Saline-Alkali Wastelands in Jodhpur District, Western Rajasthan Using Remote Sensing Techniques - Singh, N; Singh, Surendra; Sharma, K D (Annals of Arid Zone, 2016)
Application of remote sensing techniques in conjunction with ground truth for the identification, classification and mapping of natural and man-induced saline-alkali wastelands and their gensis and also morpholgical and physico-chemical characteristics of soils occurring under different geomorphic settings in Jodhpur district of western Rajasthan has been discussed in this paper. These wastelands appear in whitish grey to yellowish grey, whitish grey to dull red and milky white to dull white and light blue tones on LANDSAT TM false colour composites whereas on LANDSAT black and white products, they exhibit white to grey and dark grey tone. The genesis of natural saline-alkali wasteland is associated with the saline depressions, natural drainage channels and low lying areas and the man induced wastelands associated with older and younger alluvial plains and burried pediment had resulted due to use of canal and saline ground water for irrigation and rise of ground water table.